Perceived Risk of COVID-19 among Nurses Working in a Tertiary Level Hospital of Kathmandu: A Cross-Sectional Descriptive Study - Chapagain, Bigya; Thapa, Nirupa; Shrestha, Shaphalta (Journal of Nursing and Health Sciences Nepal, 2023)
Introduction: Nurses are at higher risk of contracting and transmitting the novel coronavirus because of their work exposure. Perceived risk plays a major role in controlling COVID-19 propagation in a healthcare setting. The objective of this study was to find out the perceived risk of COVID-19 among nurses working in a tertiary-level hospital. Methods: A cross-sectional descriptive design was adopted. One hundred forty-four nurses were selected through a simple random sampling technique. A self-administered structured questionnaire was used for data collection. Collected data were entered into Epi-data version 3.1 and transported into Statistical Package for Social Science (SPSS) version 16 for further analysis. Results: One hundred forty-four nurses participated in the study. The age group ranged from 21-54 years (mean ± SD = 28.12 ± 5.045). More than half [76 (52.8%)] were unmarried. Almost all respondents [135(93.7%)] were staff nurses. One-hundred twenty (83.3%) had not taken infection prevention and control training. Almost all respondents [139(96.5%)] had no chronic illness. Only, twenty respondents (3.5%) had maternal-related health conditions. Half of the respondents [75(52.1%)] were living with vulnerable family members. Most of the respondents [125(86.8%)] had a high level of perceived risk of COVID-19. Conclusions: The study highlights the high level of the perceived risk of COVID-19 among nurses. Most of the nurses were worried about getting COVID-19 and transmission to their loved one’s health. High levels of perceived risks lead to less effective healthcare services therefore, there is a need for appropriate intervention to address nurses’ problems in crisis time.